Addendum to Dichloromethane [BAT Value Documentation, 2016]. Issue 4 (19th October 2018) - Bolt, H.M.; Weistenhöfer, W.; Drexler, H.; Hartwig, A.; ,
Abstract: In 2015 the German Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area has re‐evaluated dichloromethane [CAS No. 75‐09‐2 ], considering dichloromethane in blood to characterize the internal exposure. In a chamber study, 14 non‐smokers were exposed to different concentrations of dichloromethane. After exposure to the present MAK value of 50 ml dichloromethane/m³ without physical activity, a concentration of 0.3 mg dichloromethane/l blood was measured. Considering an increased intake due to elevated breathing volume during work, the exposure to 50 ml dichloromethane/m³ results in a blood concentration of 0.5 mg/l. Taking into account this study and the EKA correlation of 2001, a BAT value of 500 µg dichloromethane/l blood was evaluated. Sampling time is straight after exposure.